A Study of Plate Waste in a Food Service - Yuksel, Aysun; Yılmaz Önal, Hülya (Progress in Nutrition, 2021)
Objective: To determine the amount of plate waste of the personnel eating in a hospital food hall and to evaluate according to the food types. Design: A cross-sectional trial. Setting: Food hall of a state hospital in İstanbul. Main Outcome Measures: Plate wastes by food types. Analysis: In the analysis of quantitative variables, the interactive model was tested with two-way analysis of variance (Two-way ANOVA) for the effects of 2 factors (meal and type of food). Results: During the research, 16,722 people’s plate waste was weighed. 6.2% of the edible food that was served was disposed. The average amount of waste at dinner was found to be less than lunch (p